Basal Subnuclear Vacuolization, Armanni-Ebstein Lesions, Wischnewsky Lesions, and Elevated Vitreous Glucose and β-Hydroxybuyrate: Is It Hypothermia, Diabetic Ketoacidosis, or Both?. (September 2018) - Tse, Rexson; Garland, Jack; Kesha, Kilak; Triggs, Yvonne; Yap, Zhi; Stables, Simon
Abstract : Abstract: Hypothermia and diabetic ketoacidosis are both potentially fatal conditions, which have historically been considered to have associated pathognomonic pathologies. Hypothermia and diabetic ketoacidosis share similar pathological mechanisms, which result in metabolic derangement, with increased post mortem vitreous glucose and β-hydroxybuyrate, and are able to exacerbate and precipitate one another. Although Wischnewsky lesions are associated with hypothermia, and Armanni-Ebstein lesions and basal subnuclear vacuolization are associated with diabetic ketoacidosis, recent studies have demonstrated that there is a significant overlap between the pathological findings of these 2 conditions. We report a case of a 50-year-old woman with type 1 diabetes who was found deceased in the middle of winter. Autopsy showed Wischnewsky lesions, Armanni-Ebstein lesions, and basal subnuclear vacuolization, together with elevated vitreous glucose and β-hydroxybuyrate. The cause of death was the combined effects of hypothermia and diabetic ketoacidosis. This case highlights the overlapping clinical presentation, pathophysiology, and pathology of these 2 conditions.